Lignin environment-friendly adhesive as well as preparation method and application thereof
By mixing a low co-solvent solvent system of quaternary ammonium salt surfactant and organic acid and lignin powder, the problem of difficult curing of lignin-based anti-aldehyde-free adhesive under normal temperature and pressure and insufficient bonding strength is solved, achieving a healthy and environmentally friendly and efficient wood bonding effect.
Patent Information
- Application Number
- CN202411790827.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The existing lignin-based anti-aldehyde-free adhesives are difficult to cure under normal temperature and pressure, and the bonding strength is insufficient, so they cannot completely replace traditional formaldehyde and phenol adhesives.
By mixing quaternary ammonium surfactant with organic acid under heating conditions, a low co-solvent solvent preform was formed, and lignin powder was mixed with it. The lignin powder was dispersed and dissolved by hydrogen bonding and van der Waals force to form a uniform black viscous liquid.
It realizes that lignin environmentally friendly adhesive cures under normal temperature and pressure, has an adhesive strength of ≥1MPa, is convenient to operate, and does not require high temperature and high pressure assistance, and is suitable for healthy and environmentally friendly wood bonding needs.
Smart Images

Figure BDA0005175275860000091 
Figure BDA0005175275860000101 
Figure HDA0005175275870000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of manufacturing lignin-based formaldehyde-free adhesives, and in particular to an environmentally friendly lignin adhesive and a preparation method and application thereof. Background Art
[0002] Modern home furnishing materials are mostly based on composite man-made panels, including plywood, particleboard, and fiberboard. Currently, 70% of the world's formaldehyde is used to produce urea, phenol, and melamine formaldehyde resin adhesive products. Phenolic resin adhesives used in man-made panels have disadvantages such as high cost, high brittleness, high curing temperature, free formaldehyde, and free phenol. Formaldehyde is a bulk chemical in wood products. Due to its high volatility, it is toxic to the human body and has caused a large number of environmental problems. As people's requirements for the home environment continue to increase, they are forced to seek healthy and environmentally friendly adhesives. In recent years, researchers have been committed to exploring biomass raw materials (starch, protein, lignin, and tannin) to replace phenol and formaldehyde to prepare environmentally friendly green adhesives.
[0003] Lignin is the second largest natural polymer in nature after cellulose. It primarily originates from wastewater from industrial papermaking and pulping and from biomass refinery pretreatment processes. my country produces over 10 million tons of lignin annually, with the vast majority recycled as a heat source through alkali recovery, resulting in a significant waste of this natural aromatic resource. Because lignin is a complex compound composed of aromatic ring structural units and possesses a variety of surface functional groups, such as hydroxyl, methoxy, carbonyl, and methyl, it has the potential to be developed as a bio-based material. Significant progress has been made in developing environmentally friendly lignin-based phenolic adhesives, using lignin to partially replace phenol. However, this method still uses phenol and formaldehyde, and the bonding of boards requires high temperatures and high pressures, placing significant demands on equipment and the environment. Therefore, the development of a green, formaldehyde-free, and phenol-free lignin adhesive is of great practical significance. Summary of the Invention
[0004] The main purpose of the present invention is to provide a lignin environmentally friendly adhesive and its preparation method and application. The technical problem to be solved is how to prepare a lignin environmentally friendly adhesive so that the adhesive does not contain formaldehyde and phenol substances, is healthy and environmentally friendly, and at the same time, the bonding of wood can be carried out at room temperature and pressure, the operation is convenient, and the bonding strength is excellent, so that it is more suitable for bonding needs in specific occasions.
[0005] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical solutions. According to the method for preparing a lignin environmentally friendly adhesive proposed by the present invention, the method comprises the following steps:
[0006] S1: mixing a quaternary ammonium surfactant and an organic acid, stirring them uniformly under heating conditions to obtain a transparent preformed solution;
[0007] S2: mixing the prefabricated liquid with lignin powder, stirring evenly, to obtain a lignin environmentally friendly adhesive.
[0008] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0009] Preferably, in the aforementioned preparation method, the quaternary ammonium salt surfactant is selected from at least one of 3-chloro-2-hydroxypropyltrimethylammonium chloride, benzyltrimethylammonium chloride, benzyltriethylammonium chloride and octadecyltrimethylammonium chloride; and the organic acid is selected from at least one of formic acid, acetic acid and citric acid.
[0010] Preferably, in the aforementioned preparation method, the mass ratio of the quaternary ammonium salt surfactant to the organic acid is 0.5 to 2:1.
[0011] Preferably, in the aforementioned preparation method, the solid content of the preformed liquid is ≥49% in terms of mass percentage.
[0012] Preferably, in the aforementioned preparation method, the heating temperature is 70-100°C.
[0013] Preferably, in the aforementioned preparation method, the mass ratio of the prefabricated liquid to the lignin powder is 1 to 2:1.
[0014] Preferably, in the aforementioned preparation method, the lignin powder is selected from at least one of loniflurane lignin, kraft lignin and hydrolyzate lignin.
[0015] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical solutions: According to the present invention, a lignin-based environmentally friendly adhesive is provided, which can be cured at room temperature and pressure; after curing, the lignin-based environmentally friendly adhesive has a bonding strength to wood of ≥1 MPa.
[0016] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0017] Preferably, the aforementioned environmentally friendly lignin adhesive is prepared by the aforementioned preparation method.
[0018] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical solutions: The present invention proposes an application of the aforementioned environmentally friendly lignin adhesive in the field of wood panels.
[0019] By means of the above technical solution, the environmentally friendly lignin adhesive and its preparation method and application proposed in the present invention have at least the following advantages:
[0020] The environmentally friendly lignin adhesive proposed by the present invention and its preparation method and application are as follows: a quaternary ammonium surfactant and an organic acid are mixed under heating conditions to form a low eutectic solvent through hydrogen bonding, thereby forming a uniform and stable transparent prefabricated liquid; lignin powder is then added to the prefabricated liquid and stirred, wherein the lignin powder is dispersed under the action of the quaternary ammonium surfactant, and the quaternary ammonium surfactant can also promote the organic acid to penetrate into the lignin and form hydrogen bonds with the organic acid, thereby enabling the lignin powder to be well dissolved to form a uniform black viscous liquid, namely the environmentally friendly lignin adhesive; due to the long-term stable hydrogen bonding between the quaternary ammonium surfactant and the organic acid, the quaternary ammonium surfactant and the organic acid can be in a low eutectic system for a long time, thereby making the environmentally friendly lignin adhesive of the present invention have good fluidity, making it easy to store and easy to apply; when the environmentally friendly lignin adhesive is applied to the surface of wood, the adhesive becomes thicker and thicker, and the adhesive becomes more and more sticky. When the surface is wetted, its good fluidity makes the organic acid in the lignin environmentally friendly adhesive have a strong penetration effect. The organic acid will penetrate into the interior of the wood with part of the lignin, while most of the lignin and the quaternary ammonium surfactant will remain on the surface of the wood. The lignin and the surfactant will undergo hydrogen bond cross-linking with the wood surface, which makes it have a certain mechanical strength. As the organic acid gradually penetrates into the interior of the wood, the hydrogen bond effect between it and the quaternary ammonium surfactant gradually weakens or even disintegrates, and each is restored to an independent organic acid and quaternary ammonium surfactant. As the quaternary ammonium surfactant loses its low solubility with the organic acid and gradually solidifies, the lignin environmentally friendly adhesive can be solidified under normal temperature and pressure conditions, thereby firmly bonding the wood together and having strong bonding performance. In the technical solution of the present invention, no auxiliary heating or pressurization is required when bonding the wood, and there is no need to purchase expensive professional equipment, the operation is convenient, and the cost is saved.
[0021] Furthermore, the technical solution of the present invention can be applied to a variety of industrial lignins, the raw materials thereof are from a wide range of sources, the raw materials used are safe and non-toxic, and have good biocompatibility.
[0022] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the bonding strength testing method of the present invention;
[0024] Figure 2 1 is the XRD pattern of each substance in the lignin environmentally friendly adhesive in the embodiment of the present invention. DETAILED DESCRIPTION
[0025] To further illustrate the technical means and effectiveness of the present invention in achieving its intended objectives, the following, in conjunction with preferred embodiments, provides a detailed description of an environmentally friendly lignin adhesive, its preparation method, and its specific implementation, structure, features, and effectiveness. In the following description, different references to "one embodiment" or "embodiment" do not necessarily refer to the same embodiment. Furthermore, specific features, structures, or characteristics of one or more embodiments may be combined in any suitable manner.
[0026] The present invention provides a method for preparing an environmentally friendly lignin adhesive, which comprises the following steps:
[0027] First is that quaternary ammonium salt surfactant and organic acid stir under heating condition, obtain transparent prefabricated liquid.In this step, for proterties, be the quaternary ammonium salt surfactant and the organic acid of liquid, can form uniform transparent liquid by effects such as hydrogen bond and van der Waals forces between the two; For proterties, be the quaternary ammonium salt surfactant and the organic acid of solid, although it also can form effects such as hydrogen bond and van der Waals forces at normal temperatures, because the molecular mobility of solid is restricted, cause its effect slowly, the present invention preferably makes under the auxiliary action of heating condition, can form uniform transparent liquid by effects such as hydrogen bond and van der Waals forces between the two, to improve efficiency. Between quaternary ammonium salt surfactant and the organic acid, there are chemical reactions such as hydrogen bond and van der Waals forces, but chemical reaction does not occur, new material is not formed in this step, and only be that quaternary ammonium salt surfactant and organic acid have formed the deep eutectic solvent ligand by effects such as hydrogen bond and van der Waals forces, reduce the fusing point of system, even make it still can stably store with liquid form after being cooled to normal temperature state, form transparent prefabricated liquid liquid.
[0028] In the above steps, in order to ensure that quaternary ammonium salt surfactant and organic acid can fully act, more hydrogen bonds and van der Waals forces are formed, and the present invention preferably should be fully stirred for at least 2 hours when the two are mixed. If stirring time is too short, then enough hydrogen bonds and van der Waals forces may not yet be formed between the two, causing the low eutectic solvent system formed to be insufficient; and if stirring time is too long, it is not necessary for the dimension consideration of energy conservation, therefore in subsequent embodiments of the present invention, all fixed stirring time is 2 hours.
[0029] After a large number of experimental tests, it was found that when the quaternary ammonium salt surfactant is selected from at least one of 3-chloro-2-hydroxypropyltrimethylammonium chloride, benzyltrimethylammonium chloride, benzyltriethylammonium chloride and octadecyltrimethylammonium chloride, and the organic acid is selected from at least one of formic acid, acetic acid and citric acid, the low eutectic solvent system formed by the two is particularly stable after being matched with each other, and can be stably stored at room temperature for a long time, which is beneficial to the storage of the adhesive.
[0030] In the above steps, the quaternary ammonium surfactant and organic acid are preferably prepared from raw materials with higher purity. In this case, the high concentration of the raw materials can form more intensive hydrogen bonds and van der Waals forces, resulting in a more effective preformed liquid. However, some raw materials, such as 3-chloro-2-hydroxypropyltrimethylammonium chloride, are more expensive when they are high in purity. Therefore, the present invention uses commercially available raw materials with a mass concentration of 65%. Based on the cost-effectiveness of different raw materials available on the market, and taking into account factors such as the bonding performance and sizing cost of the final adhesive product, the present invention preferably has a mass solids content of ≥49% for the preformed liquid. When the solids content meets this condition, the preformed liquid can be used to prepare lignin-based environmentally friendly adhesives with excellent performance indicators. Furthermore, the applicant has found that as the solids content of the preformed liquid increases, the bonding performance of the final lignin-based environmentally friendly adhesive improves, the bonding time is shortened, and the efficiency is higher. Therefore, the present invention further prefers that the mass solids content of the prepared preformed liquid be ≥78%. However, the increase in the solid content of the preformed liquid will gradually increase its viscosity. As the viscosity of the preformed liquid increases, the spreadability of the adhesive will gradually decrease, resulting in an increase in the amount of glue applied, which in turn increases the cost. In view of this, the present invention preferably has a mass solid content of 78-85% for the preformed liquid, which can ensure a better balance between its performance, efficiency and cost. The amount of glue applied is preferably 12-18 g / m 2 .
[0031] In the above steps, in order to enable the quaternary ammonium salt surfactant and the organic acid to form sufficient hydrogen bonds and van der Waals forces, the molecular numbers of the two should be basically matched to avoid the difficulty in forming a deep eutectic solvent due to the small amount of one of the raw materials, which in turn increases the difficulty of forming the prefabricated liquid; for this reason, the present invention preferably has a mass ratio of the quaternary ammonium salt surfactant to the organic acid of 0.5 to 2:1; when the ingredients are mixed within this ratio range, more hydrogen bonds and van der Waals forces can be formed between the two, and the formed deep eutectic solvent ligand is more stable.
[0032] In the above steps, due to the differences in the properties of different quaternary ammonium salt surfactants and organic acids, in order to ensure that each of the above-mentioned compatibility combinations can rapidly form a deep eutectic solvent ligand, the preferred heating temperature of the present invention is 70 to 100° C. When the heating temperature is low, the molecular activity of some raw materials is restricted, thereby limiting the hydrogen bonds and van der Waals forces between the quaternary ammonium salt surfactant and the organic acid, which is uneconomical in terms of efficiency; and when the temperature is too high, it may cause energy waste. The selection of the heating temperature only affects production efficiency and energy consumption, and has little impact on the bonding properties of the adhesive. For the convenience of data comparison, the fixed heating temperature in the subsequent examples is 80° C.
[0033] After the prefabricated liquid is prepared, the prefabricated liquid is mixed with lignin powder, and stirring is performed to obtain the lignin environmentally friendly adhesive. In the above steps, the interpolation of lignin powder does not need to be added step by step, and the disposable lignin powder is all added to ensure that it is fully dissolved. This is because the prefabricated liquid comprises a large amount of quaternary ammonium surfactants, and lignin powder is dispersed under the effect of the quaternary ammonium surfactants. The quaternary ammonium surfactants can also promote organic acid to penetrate into the lignin and form hydrogen bonds with it simultaneously, thereby making lignin powder preferably dissolved, forming a uniform black viscous liquid is the lignin environmentally friendly adhesive.
[0034] After a large number of experimental tests, it can be seen that when the mass ratio of the prefabricated liquid to the lignin powder is in the range of 1 to 2:1, the spreadability, curing time, and bonding strength of the resulting adhesive are particularly excellent.
[0035] In the above technical solution, lignin powder does not react chemically with quaternary ammonium surfactants and organic acids, and they only interact with each other through hydrogen bonds and van der Waals forces. Specifically, lignin powder is dispersed under the action of quaternary ammonium surfactants, and quaternary ammonium surfactants can also promote the penetration of organic acids into lignin to form hydrogen bonds with lignin, thereby enabling lignin powder to be better dissolved; therefore, the structure and groups of lignin itself have little effect on the adhesive, thereby enabling the technical solution of the present invention to be applicable to a variety of industrial lignins; considering the source availability and cost considerations of lignin powder, the present invention preferably selects lignin powder from at least one of alkali lignin, sulfate lignin and hydrolyzate lignin. The raw material source of lignin powder is wide, safe and non-toxic, and has good biocompatibility.
[0036] In order to illustrate the technical solution of the present invention, the present invention uses an adhesive system of alkali lignin, formic acid, and benzyltriethylammonium chloride to perform XRD diffraction pattern testing. The results are shown in the attached figure. Figure 2 As shown in (a) and (b); the horizontal axis is the diffraction angle 2-Theat (Bragg angle), in degrees, which is used to reflect the diffraction direction of different crystal planes in the crystal; the vertical axis Intensity is the diffraction intensity, in arbitrary units, which is used to represent the intensity of the diffraction peak at the corresponding diffraction angle. The intensity is related to factors such as crystal structure and composition. AL shown in the figure is alkali lignin, FA is formic acid, and AL -F It is a mixture of alkali lignin and formic acid, TEBAC is benzyltriethylammonium chloride, AL -F-T It is a mixture of alkali lignin, formic acid and benzyltriethylammonium chloride. -T It is a mixture of alkali lignin and benzyltriethylammonium chloride.
[0037] Add AL to FA to obtain AL -F mixture, consisting of Figure 2 As shown in (a), AL -F The diffraction peaks of the mixture are basically consistent with those of FA, which indicates that the intermolecular hydrogen bonding of AL is weakened and that AL -F No new diffraction peaks appeared in the mixture system, that is, no new substances were formed; compared with FA, AL -F The diffraction peak intensities of the system at 13° and 29.8° were slightly reduced; the above results indicate that FA weakens the intermolecular hydrogen bonds of AL, while AL only slightly changes the crystal structure of FA. There is less covalent cross-linking reaction between FA and AL, and no new chemical structure is formed between the two.
[0038] Add AL to TEBAC to obtain AL -T System, by the Figure 2 As shown in (b), AL -T A new diffraction peak appeared in the system, which on the one hand indicated that the intermolecular hydrogen bonding of AL was weakened, and on the other hand indicated that a new peak shape was formed between the strong crystal structure of TEBAC and AL. The above results indicate that there is a strong covalent cross-linking reaction between TEBAC and AL.
[0039] By the attached Figure 2 As shown in (b), compared with AL -T system, after TEBAC, FA and AL joined together, AL -F-T The intensity of the crystal peak of the system is significantly reduced; studies have shown that covalent cross-linking reactions will hinder the formation of an ordered crystal structure; therefore, AL -F-T The intensity of the crystal peak of the system is significantly reduced, indicating that the mixed system with the three added together forms the most cross-linking reaction.
[0040] In summary, the addition of TEBAC and FA will greatly weaken the intermolecular hydrogen bonds of AL, while forming new free intermolecular hydrogen bonds, destroying the crystal form of AL and ultimately making AL -F-T The system appears to be a viscous mixed liquid state.
[0041] After the above viscous mixed liquid is evenly applied on the wood board, the small amount of water brought by FA dries in the air, and the free intermolecular hydrogen bonds are closely arranged between the wood molecules, showing an AL -F-T Adhesive effect with wood.
[0042] The present invention also provides a lignin environmentally friendly adhesive prepared by the above-mentioned preparation method, which can be cured at room temperature and pressure; the bonding strength of the lignin environmentally friendly adhesive to wood after curing is ≥1MPa.
[0043] The present invention also provides an application of the aforementioned environmentally friendly lignin adhesive in the field of wood panels. The wood panels prepared using the environmentally friendly lignin adhesive do not contain formaldehyde or phenolic substances, are healthy and environmentally friendly, and can be bonded together at room temperature and pressure, making the process easy and providing excellent bonding strength.
[0044] The present invention will be further described below with reference to specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Non-essential improvements and adjustments made to the present invention by those skilled in the art based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0045] Unless otherwise specified, the materials and reagents mentioned below are commercially available products familiar to those skilled in the art. Unless otherwise specified, the methods described are all well-known methods in the art. Unless otherwise defined, technical or scientific terms used shall have the same meanings as those commonly understood by those skilled in the art.
[0046] Example 1
[0047] This embodiment prepares a lignin environmentally friendly adhesive, and the specific steps are as follows:
[0048] 1) Prepare the adhesive pre-liquid: Mix benzyltriethylammonium chloride and formic acid at a mass ratio of 1:1 at 80°C, stir evenly, and store at room temperature for later use;
[0049] 2) Mix the adhesive prefabricated liquid with Longli Industrial lignin powder in a mass ratio of 2:1, stir evenly, and add a small amount of water to adjust its solid content to obtain a black mixed viscous liquid, which is the lignin environmentally friendly adhesive. It can be stored at room temperature for future use.
[0050] The bonding performance of the environmentally friendly lignin adhesive prepared in this example was tested in the following steps:
[0051] 1) Cut the beech wood into strips with a width of 20 mm, a length of 80 mm, and a thickness of 5 mm;
[0052] 2) Apply the lignin environmentally friendly adhesive on ten beech boards. The coating area of the lignin adhesive on each beech board is 20mm×10mm, and the amount of adhesive applied is 15g / m 2 ;
[0053] 3) Place the coatings on two beech boards together and fix them with clips. Leave them at room temperature for 24 hours.
[0054] 4) According to the single-layer lap joint specimen in BS EN 205:2016 timber lap joint method, use a universal tensile testing machine to perform parallel tension and shear tests, as shown in the attached Figure 1When clamping the specimen into the tensile testing machine, shims or appropriately designed grips should be used to ensure that the force is applied in the plane of the joint line and centered, with Figure 1 In the figure, l1 represents the length of the test specimen, which is 150 mm ± 2 mm; b represents the width of the test specimen, which is 20 mm ± 0.2 mm; l3 represents the length of the test specimen, which is 80 mm ± 2 mm; s represents the thickness of the test specimen, which is 5 mm ± 0.1 mm; l2 represents the bonding length of the test specimens overlapping each other, which is 10 mm ± 0.2 mm.
[0055] The bonding strength of the environmentally friendly lignin adhesive prepared in this example is 4.36±0.13 MPa. The mass solid content is tested using conventional methods in the art.
[0056] Examples 2 to 16
[0057] The same as Example 1, except for the types and ratios of raw materials in the lignin environmentally friendly adhesive, as shown in Table 1; the test results are shown in Table 1.
[0058] Comparative Example 1
[0059] The Longli Industrial lignin powder was mixed with formic acid to obtain a black mixed liquid, which was then stored at room temperature. The test was performed according to the test method shown in Example 1, and the test results are shown in Table 1.
[0060] Comparative Example 2
[0061] The Longli Industrial Lignin powder was mixed with deionized water to obtain a black mixed liquid, which was then stored at room temperature. The test was performed according to the test method shown in Example 1, and the test results are shown in Table 1.
[0062] Comparative Example 3
[0063] Longli Industrial Lignin Powder and Benzyltriethylammonium Chloride were stirred evenly to obtain a black mixed liquid, which was then stored at room temperature. Testing was performed according to the test method shown in Example 1, and the test results are shown in Table 1.
[0064] Table 1
[0065]
[0066]
[0067] The test results of the above examples and comparative examples show that the adhesives prepared by the technical solution of the present invention have excellent bonding properties, and their bonding strength after curing at room temperature and pressure is ≥1 MPa, as shown in Examples 1 to 16. Furthermore, when formic acid is preferably the organic acid, the bonding strength can be as high as 3 MPa or above, as shown in Examples 1 to 8 and Examples 11 to 16. However, when only a surfactant is added without an organic acid, the adhesive has certain bonding properties but low bonding strength, as shown in Comparative Example 3. Furthermore, when only an organic acid is added without a surfactant, the adhesive has no bonding strength, as shown in Comparative Example 1. When neither an organic acid nor a surfactant is added, the adhesive has no bonding strength, as shown in Comparative Example 2.
[0068] It can also be seen from the test results of the above embodiments and comparative examples that the adhesive prepared by the technical solution of the present invention has better bonding performance when the solid content is ≥49%, such as in Examples 1 to 16; further, when the solid content is ≥78%, while the bonding performance is better, the drying speed of the adhesive is faster and the construction efficiency is improved, such as in Examples 1, 3 to 6, 8 to 10, and 12 to 16.
[0069] The technical features in the claims and / or the specification of the present invention may be combined, and the manner of combination is not limited to the combination obtained by reference in the claims. The technical solutions obtained by combining the technical features in the claims and / or the specification are also within the scope of protection of the present invention.
[0070] The above description is merely a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Any simple modifications, equivalent changes and modifications made to the above embodiment based on the technical essence of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a lignin environmentally friendly adhesive, characterized in that: It includes the following steps: S1: mixing a quaternary ammonium salt surfactant and an organic acid, and stirring them evenly under heating conditions to obtain a transparent preformed liquid; S2: mixing the prefabricated liquid with lignin powder, stirring evenly, to obtain a lignin environmentally friendly adhesive.
2. The preparation method according to claim 1, characterized in that: The quaternary ammonium salt surfactant is selected from at least one of 3-chloro-2-hydroxypropyltrimethylammonium chloride, benzyltrimethylammonium chloride, benzyltriethylammonium chloride and octadecyltrimethylammonium chloride; the organic acid is selected from at least one of formic acid, acetic acid and citric acid.
3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the quaternary ammonium salt surfactant to the organic acid is 0.5-2:
1.
4. The preparation method according to claim 1, characterized in that: Calculated by mass percentage, the solid content of the prefabricated liquid is ≥49%.
5. The preparation method according to claim 1, characterized in that: The heating temperature is 70-100°C.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the prefabricated liquid to the lignin powder is 1-2:
1.
7. The preparation method according to claim 1, characterized in that: The lignin powder is selected from at least one of loniflurane lignin, kraft lignin and hydrolyzate lignin.
8. A lignin environmentally friendly adhesive, characterized in that: It can be cured at room temperature and pressure; the bonding strength of the lignin environmentally friendly adhesive to wood after curing is ≥1MPa.
9. The environmentally friendly lignin adhesive according to claim 8, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.
10. Use of the environmentally friendly lignin adhesive according to claim 8 or 9 in the field of wood panels.
Citation Information
Patent Citations
Preparation method of eutectic ionic liquid modified lignin-phenolic resin
CN105504191A
Acidic deep-eutectic solvent, preparation thereof and application of acidic deep-eutectic solvent in pretreatment of straws and improvement of enzymolysis efficiency
CN112899313A
Method for improving amination modification efficiency or phenolic hydroxyl group content of alkali lignin
CN113698624A
Lignocellulose pulping method based on acidic eutectic solvent
CN114086414A
Eutectic solvent as well as preparation method and application thereof
CN114835921A